Proceedings. 16th International Conference on Scientific and Statistical Database Management, 2004.
DOI: 10.1109/ssdm.2004.1311214
|View full text |Cite
|
Sign up to set email alerts
|

On the integration of autonomous data marts

Abstract: We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…In [8] we have shown that the satisfaction of this property prevents inconsistencies between aggregations computed over d and aggregations computed over E(d).…”
Section: An Algebra For Dimensionsmentioning
confidence: 96%
See 2 more Smart Citations
“…In [8] we have shown that the satisfaction of this property prevents inconsistencies between aggregations computed over d and aggregations computed over E(d).…”
Section: An Algebra For Dimensionsmentioning
confidence: 96%
“…Intuitively, two dimensions of different data marts are compatible if their common information is consistent. In a preliminary study [8], we have shown that dimension compatibility gives the ability to correlate, in a correct way, multiple data marts by means of drillacross queries [17], which are basically joins, over common dimensions, of different data marts.…”
Section: Goal and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having dimension tables that are shareable is crucial because it will provide the capability of each data mart integrated with and connected to each other [10]. In particular, the integration of data marts will rely on a common variation of the dimensions of the existing used together at each data marts as a reference in the OLAP reporting will be done.…”
Section: Dimension Sharing Integrationmentioning
confidence: 99%
“…Bottom-Up Data Warehouse coupled with Bus Scheme for the integration and transformation of data into the data mart will be a practical solution when the company did not know the structure of future operational systems and operational systems in each section constructed independently (autonomous) [10].…”
Section: Introductionmentioning
confidence: 99%